Contextualizing compliance officers and their state of practice - Krambia-Kapardis, Maria; Stylianou, Ioanna; Demetriou, Salomi (My University, 2019)
The compliance officers' (CO) profession has been evolving over the last few decades. The expectations placed upon the individuals holding such a position vary across jurisdictions, but they are all expected to ensure employees and management of the business entity comply with the law. Given the limited research on CO in Europe, and the increasing public interest in this profession, the current authors have carried out a survey in Cyprus in an effort to map out and contextualize the CO' profession. The findings illustrate CO's academic and professional qualifications, their awareness of their legal liability, the level of knowledge and job performance of their duties as prescribed by law, as well as gaps in the performance of duties as expected by management, boards, and regulators. The policy implications derived from the study suggest coherence and synergies to be found through common exam and postgraduate qualification in the field of financial compliance.
Keywords: Compliance officers; Knowledge gap; Legal duties; Liabilities; Responsibilities